2012
DOI: 10.1089/ham.2012.1030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Scoring Systems for Assessment of Acute Mountain Sickness

Abstract: The purpose of this study was to compare three commonly used scoring systems of acute mountain sickness (AMS)-the 5-item Lake Louise Self-report (LLS), the 11-item abridged version of the Environmental Symptoms Questionnaire (ESQ-III), and a 100 mm visual analog scale (VAS)-on climbers (N=63; 34.6±9.9 years) making a 1-day ascent of a 5640 m peak after a rest of ~10 h at 4260 m. The prevalence of AMS was 63% when defined as LLS ≥3, 49% when defined as either LLS ≥5 or ESQ-III ≥0.7, and 41% when defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…We note the conclusions of others that suggest the best system for AMS assessment remains undetermined and that further work to re-evaluate the optimal cut-offs for research is required. 6,29,30 SUMMIT SUCCESS The rate of summit success in our cohort was high, with 88% reaching Uhuru Peak (5895 m), and 94% achieving Gilman's Point (5861 m) or above. This is in contrast to success rates of 51% and 61% in previous research on 4and 5-day ascents.…”
Section: Amsmentioning
confidence: 70%
“…We note the conclusions of others that suggest the best system for AMS assessment remains undetermined and that further work to re-evaluate the optimal cut-offs for research is required. 6,29,30 SUMMIT SUCCESS The rate of summit success in our cohort was high, with 88% reaching Uhuru Peak (5895 m), and 94% achieving Gilman's Point (5861 m) or above. This is in contrast to success rates of 51% and 61% in previous research on 4and 5-day ascents.…”
Section: Amsmentioning
confidence: 70%
“…Using an LLQS score of 5 or greater as the reference standard for establishing a diagnosis of AMS (Table 4) Abbreviations: AMS, acute mountain sickness; AMS-C, AMS-Cerebral score; LLQS, Lake Louise Questionnaire Score. The number of studies was too low for meaningful meta-regression of the Hackett clinical score with a different cutoff (Ն2; 4 studies 34,48-50 ), the visual analog scale score (4 studies with only 2 allowing prevalence analysis 45,46 ), the clinical functional score (2 studies 22,47 ), and the LLQS (Ն7 points; 1 study 51 ). c Some studies reported more than 1 instrument at a given altitude, explaining why the total number of studies for pooled analyses is greater than the number of included studies (91).…”
Section: Performance Of Acute Mountain Sickness Diagnostic Instrumentsmentioning
confidence: 99%
“…The data markers represent the size of each study. For indicative purpose, the few data points available for the instrument-in-comparison studies (visual analog scale score 45,46 and clinical functional score 22,47 ), not included in the meta-regression, are also shown. Detailed results of pooled analyses are shown in Table 2.…”
Section: Chinese Scorementioning
confidence: 99%
“…The second questionnaire, developed by a consensus committee, consists of five self-reported items and is known as the Lake Louise Self-report (LLS) [7]. There is no single gold-standard assessment tool [8, 9] and, unfortunately, the two questionnaires do not always produce the same diagnosis [10]. …”
Section: Introductionmentioning
confidence: 99%